2017
DOI: 10.2174/221028901708010052
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Pain Management: Morphine Combined with Omega-3 Fatty Acids

Abstract: Abstract:The treatment of acute and chronic severe pain remains a common major challenge faced by clinicians working with the general population, and even after the application of recent advances to treatments, there may still continue to be manifestations of adverse effects.Chronic pain affects the personal and social life of the patient, and often also their families. In some cases, after an acute pain the patient continues to experience chronic pain, which can be a result of diseases such as cancer.Morphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been shown that morphine-induced behavioral and cellular adaptations are markedly prevented by O3 treatment (Hakimian et al, 2017). Consistently, some studies have suggested the use of combined morphine-O3 therapy for pain management (Laino, 2017). On the other hand, there are evidence indicating that O3 supplementation prevents and sometimes reverses ethanol-induced complications in multiple systems.…”
mentioning
confidence: 88%
“…Furthermore, it has been shown that morphine-induced behavioral and cellular adaptations are markedly prevented by O3 treatment (Hakimian et al, 2017). Consistently, some studies have suggested the use of combined morphine-O3 therapy for pain management (Laino, 2017). On the other hand, there are evidence indicating that O3 supplementation prevents and sometimes reverses ethanol-induced complications in multiple systems.…”
mentioning
confidence: 88%
“…Omega 3 especially EPA has a long-chain structure equation with arachidonic acid (AA), thus it can be a competitor to replace arachidonic acid in the metabolic processes of cyclooxygenase (COX) and lipoxygenase (Kobayashi et al, 2006). This theory is strengthened by another study by Laino (2017), suggested that EPA can inhibit the COX mechanism, therefore, prostaglandins are not formed. Blockage of the COX enzyme would inhibit the conversion of AA to the proinflammatory PGs that mediate fever (Maroon and Bost, 2006).…”
Section: Antipyretic Effectmentioning
confidence: 99%
“…and through modulation of central µ‐opioid receptors in diabetic neuropathy . In addition, different types of ω‐3, such as EPA plus DHA, ALA and DHA, have an analgesic effect …”
Section: Introductionmentioning
confidence: 99%